Estimation of biogenic VOC emissions and its impact on ozone formation over the Yangtze River Delta region, China. (August 2018) - Liu, Yan; Li, Li; An, Jingyu; Huang, Ling; Yan, Rusha; Huang, Cheng; Wang, Hongli; Wang, Qing; Wang, Min; Zhang, Wei
Abstract: Biogenic volatile organic compounds (BVOCs) play an important role in the formation of tropospheric ozone. In the present work, biogenic emissions over the Yangtze River Delta (YRD) region for year 2014 were developed based on the interpretation of remote sensing image and MODIS data using the Model of Emissions of Gases and Aerosols from Nature (MEGAN). Impact of BVOCs emissions over the YRD region on ozone formation was investigated based on the Weather Research and Forecasting (WRF)-Community Multi-scale Air Quality (CMAQ) modeling system for July 2014. Two parallel scenarios-with and without BVOCs emissions-were developed to evaluate the influence of BVOCs emission on ozone formation. Biogenic emissions were estimated to be 18.86 × 10 5 ton yr −1 over the YRD region for year 2014, with higher emissions in the southern YRD region than the northern region, and higher emissions in summer than other seasons. Model evaluation showed fairly good model performances, with the index of agreement (IOA) of meteorological parameters and ozone concentrations of 0.80–0.95 and 0.76–0.91, respectively. Ozone concentrations mainly concentrated in the northwest, which is the downwind of the YRD region in summer. Impact of biogenic emissions on ozone formation exhibited a strong spatial pattern: high contributions were observed in the middle YRD region, including Bengbu, Tongling, Hefei, Huzhou, Nanjing and Zhenjiang, with the maximum hourly ozone contribution of 18.43–36.18μg/m 3 during July 18 to 23. Ozone concentrations in rural areas would be more likely to be influenced by BVOCs emissions than urban areas. Graphical abstract: Image 1 Highlights: BVOCs emissions over the YRD region was estimated based on the interpretation of remote sensing image and MODIS data using MEGAN. Impact of BVOC emissions on ozone formation was investigated based on the WRF - CMAQ modeling system. BVOCs emissions over the YRD in 2014 were 18.86 × 10 5 ton yr −1 and mainly concentrated in southern YRD. The impact of BVOCs on ozone is mainly concentrated in the middle part of the YRD region, which is the downwind of the region in summer period.